Strategi Peningkatan Profesionalisme Guru dalam Pembelajaran - Nidawati Nidawati (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
Teacher professional development and development must be in line with similar activities for education staff in general. In the learning process, teachers play a very strategic role within the framework of carrying out their functions and realizing national education goals, where students are future human beings who are expected to be able to master science and technology, be skilled, have national character and character, and become religious people. The role of the teacher can hardly be replaced by another, especially in a multicultural and multidimensional society, where the role of technology to replace teacher tasks is still minimal. Even if sufficient learning technology is available, the real role of the teacher will not be replaced. The history of education in Indonesia has recorded that the teaching profession is a profession whose importance is recognized and its strategic role is recognized for the future development of the nation.